[Fol. 07 recto] - (:unkn) unknown (My University, 1722)
[Former shelf mark Q.5.12] --- Rev Questeborne was domestic chaplain to the Earl of Galway, and vicar of Burnchurch, co Kilkenny, 1716-29. TCD MS 2207 is also by his hand.
A true collection of severall letters on various subjects & c. written by severall persons and on various incidents
Part of the county of Kilkenny.
Keywords: Plantation records; Cartography; Ireland ?- History -- 18th century; Plantations -- Ireland; Kilkenny (Ireland : County); Maps 1720-1730